The Position and Authority of the State Audit Board in the Indonesian Constitutional Structure - M. Afif Hasbullah (International Journal of Science and Society, 2019)
This study aims to analyze the position and authority of the Supreme Audit Agency's audit in the Indonesian state administration structure. The research method used is the juridical-normative concept. This research uses statutory law materials and legal journals that have the subject of State Finance Law. This research was also conducted by analyzing the primary legal material, namely by examining theories, concepts, legal principles and legislation related to State Finance Law. Based on the study and analysis of legal sources, it can be concluded that the position of the Supreme Audit Agency of the Republic of Indonesia in the state administration system is a state institution whose authority is granted by the 1945 Constitution of the Republic of Indonesia (constitutionally entrusted power) so that it can be called the main state organ or the primary state agency. The State Audit Board has the authority to carry out audits of state and regional financial management as mandated in Article 23E of the 1945 Constitution of the Republic of Indonesia and Law Number 15 of 2006 concerning the State Audit Board.